Profiling of fecal analytes as a potential biomarker in rheumatoid arthritis - Wang, Zhiyi; Shi, Yujia; Yang, Yachen; Gong, Bangdong; Xie, Jianmin (Frontiers in Immunology, 2025)
BackgroundLoss of gut barrier integrity has been observed in rheumatoid arthritis (RA). While systemic inflammation in RA has been extensively investigated, intestinal-specific inflammatory processes remain poorly understood. This study is designed to identify a novel biomarker panel combining fecal cytokine profiles with gut barrier biomarkers to discriminate RA patients with varying disease progression.MethodsFeces (Fc) and plasma (Pl) were obtained from 62 Naive RA patients (NA), 47 remission RA patients (RE), 28 difficult-to-treat RA patients(D2T), and 70 healthy controls (HC). A panel of 12 cytokines and gut barrier markers, including intestinal Fatty-Acid-Binding Protein-2 (FABP2), zonulin, Hypoxia-Inducible Factor-2α (HIF-2α), D-lactate, LBP and fecal calprotectin (FCAL), was quantified by ELISA. Statistical integration with clinical parameters was performed using univariate and multivariate approaches.ResultsNA and D2T patients demonstrated marked elevations in fecal pro-inflammatory cytokines compared to RE and HC groups, including IL-6, Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF), IL-1 beta (IL-1β), Interferon-gamma (INF-γ), IL-23, Tumor Necrosis Factor-Alpha (TNF-α), IL-21, IL-17A/F, and IL-22. Fecal zonulin and plasma HIF-2α were significantly elevated in both NA and D2T groups, whereas fecal D-lactate showed a pronounced decrease in the NA and D2T groups. These biomarkers demonstrated the strongest correlation with disease severity indices. Receiver operating characteristic (ROC) analysis revealed that fecal FABP2, zonulin and D-lactate exhibited superior discriminative capacity between the NA and RE groups. whereas fecal zonulin showed remarkable diagnostic potential for distinguishing NA from D2T groups compared to plasma counterparts. The discriminant scores (DS) model incorporating fecal zonulin and plasma HIF-2α demonstrated superior discriminatory performance between the D2T and NA groups compared to the model utilizing the top five plasma parameters.ConclusionsOur fecal profiling methodology provides novel insights into the gut mucosal cytokine microenvironment during RA progression. The dissociation between fecal and plasma inflammatory profiles underscores the critical importance of localized gut immune monitoring in RA management.